Unidade de ensino potencialmente significativa voltada ao ensino de proteínas com base na produção de tofu - Souza, Angelo Pinto de (2024)
The lack of contextualization, applicability and memorization of concepts are problems frequently raised in the area of ​​Chemistry teaching. Teaching that involves contemporary themes as a way of providing students with the opportunity to identify the complex relationships between science and the real world and develop a civic stance. Thus, the objective of this research was to analyze the application of a didactic sequence with the structure of a UEPS (Potentially Significant Teaching Unit), involving food science and technology, regarding its potential to promote significant learning of protein concepts. With this, we intend to answer the following question: What are the implications that a UEPS involving tofu production can provide for learning the topic of proteins? Thus, the educational product proposed in this work is a didactic sequence structured in the steps of a UEPS, which is based on Ausubel's Theory of Significant Learning (TAS). In addition, the Science, Technology and Society (STS) approach was adopted, which also guided the selection of the proposed activities. The educational product was developed in a state school in the municipality of Herval D'Oeste - SC, together with a class of 18 students in the 3rd year of high school. The didactic sequence used scientific dissemination texts (TDC) and the production of tofu as a practical activity to address concepts related to proteins. The research was qualitative and quantitative in nature, of the action research type, and the data collection instruments were pre-test and post-test and the teacher's logbook. Data analysis regarding systematization and learning progress was done using mind maps and by comparing the responses between the pre-test and post-test, respectively. In the mind maps, all the subjects started with proteins as the central category, relating, for the most part, the topic of protein structure, which was extensively worked on in practice. The comparison between the pre-test and post-test provided a better rate of correct answers, demonstrating an improvement in learning. With the data obtained, the teacher-researcher was able to conclude that the adopted theme, the production of tofu, as well as the structuring that a UEPS offers, led to satisfactory learning, in addition, it developed good acceptance by the students, increasing engagement and motivation. UEPS, the educational product developed, will be available on the website of the Postgraduate Program in Science and Mathematics Teaching (PPGECM), link to educational products, and on the EduCapes portal under the number http://educapes.capes.gov.br/handle/capes/92093.